Immunophenotype of Kawasaki Disease: Insights into Pathogenesis and Treatment Response - Aikaterini Agrafiotou; Evdoxia Sapountzi; Angeliki Margoni; Lampros Fotis (Life)
Kawasaki disease (KD) is a systematic inflammatory condition that results in vasculitis and possible progression to the development of coronary artery lesions if left untreated. Disease pathogenesis is not fully understood, and diagnosis is based on clinical symptoms, with limited reliability considering that KD progression is time sensitive. This is further complicated by the shared clinical characteristics with other febrile diseases. Early diagnosis and prompt treatment start are associated with good prognosis in most patients. However, up to 20% of patients are resistant to available therapeutic agents and would benefit from alternative regimens. Therefore, identification of biomarkers that can provide insights on disease pathogenesis are necessary to enable early diagnosis and initiation of treatment, as well as to predict treatment responses. To this end, immunophenotyping, most commonly by flow cytometry, has been crucial in identifying central factors in KD pathogenesis. The available literature on such factors is vast and may include contradictory findings. Therefore, we aimed to summarize the available literature of the last decade on the immunophenotype of KD, focusing on biomarkers associated with disease pathogenesis and those associated with treatment response. Our review highlights the role of cells of both the innate and adaptive immune system in disease pathogenesis, as well as the role of various secreted and cell surface proteins, including inflammatory cytokines, chemokines, complement receptors, and chemoattractants both in KD pathogenesis and in treatment response.